2007
DOI: 10.3892/or.18.4.1015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of retinoic acid and IIF on growth, migration and invasiveness in the U87MG human glioblastoma cell line

Abstract: Glioblastomas, the most malignant and prevalent brain tumors which remain incurable, are characterized by both extensive proliferation and invasive growth. We previously reported a remarkable antitumoral effect of the retinoid 6-OH-11-O-hydroxyphenantrene (IIF) on neuroblastoma, leukemia and colon carcinoma cells. In this study we examined the effect of IIF on proliferation, apoptosis and cell invasion in the human glioblastoma cell line U87MG, in comparison with all-trans-retinoic acid (RA). Our results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…These results indicate that ATRA may also regulate the migration and invasion of glioma cells using alternate mechanisms. Previous studies have reported that ATRA can inhibit the activity of MMP-2 (20) and MMP-9 (15) via tissue inhibitor of metalloproteinase, a protein that may be involved in the regulation of migration and invasion of ATRA-treated glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that ATRA may also regulate the migration and invasion of glioma cells using alternate mechanisms. Previous studies have reported that ATRA can inhibit the activity of MMP-2 (20) and MMP-9 (15) via tissue inhibitor of metalloproteinase, a protein that may be involved in the regulation of migration and invasion of ATRA-treated glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding recalls recent data showing that RXR ligands are endowed with higher antitumor efficacy compared with RAR ligands. 23 Such molecules selectively target tumor cells without inducing the typical in vivo side effects of retinoids. 21,38 Moreover, we found that PGZ, a ligand of PPARg, is the least active molecule among the NR agonists tested, thus showing that NRs agonists are not interchangeable in their potential biological activity on breast CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…20 6-OH-11-Ohydroxyphenanthrene (IIF) is a recently developed RXR ligand that activates the retinoid X response element (RXRE) and exerts higher antitumor effects compared with RA without measurable side effects. [21][22][23] The RAR ligand RA activates the retinoic acid response element (RARE), which function is mediated by RAR homodimers, as well as by RAR-RXR heterodimers. 20 RXR receptors regulate gene expression by forming heterodimers with peroxisome proliferator activated receptors (PPAR a, b and g).…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic strategies for glioblastoma include surgery, radiation therapy and chemotherapy. However, the median survival of glioblastoma patients is extremely poor (3).…”
Section: Introductionmentioning
confidence: 99%